(untitled) (Psychology Travelogs, 2025)
The article highlights the peculiarities of parents’ attitudes towards themselves and their children with autism spectrum disorders. It is emphasised that parental attitudes as an object of psychological research include a combination of cognitive, emotional and behavioural components. It has been found that parents of children with autism are less confident in themselves, experiencing internal conflict, which affects the quality of emotional connection with the child. If a child has a developmental disability, it is the family that determines the success of the child’s adaptation and integration into society. It has been shown that mothers and fathers have different attitudes towards a child with ASD. The family plays an important role in the formation and development of a child’s personality, awareness of their place in the family and society, and their attitude to the world and themselves. Families raising children with autism spectrum disorders often lack the necessary knowledge about the specifics of the disorder, methods of teaching, correcting children’s behaviour, and ways to interact with a child with autism. Finding themselves in a difficult life situation, parents experience stress, which destroys the carefree world with dreams of a happy future in which the couple lived yesterday. Depression, despair, anger often manifest themselves as harshness in the treatment of children. The family avoids friendly contacts and eventually finds itself in isolation. In such situations, both adults and children need support and help, which can and should be provided in a timely manner. In such a situation, it is impossible to help a child, because the effectiveness of correctional intervention depends on the quality of family functioning, the well-being of parents, and their psychological health.